(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
A significant phase in the protection of the financial interests of European Union has been completed within adoption of Directive (EU) 2017/1371 of the European Parliament and of the Council of 5 July 2017 on the fight against fraud to the Union’s financial interests by means of criminal law, as well as the Council Regulation (EU) 2017/1939 of 12 October 2017 implementing enhanced cooperation on the establishment of the European Public Prosecutor’s Office (“the EPPO”). The purpose of this paper is to determine the extent to which national criminal law is harmonized with the recent European legislation in the field of the protection of the Union’s financial interests and to detect what steps should be taken in order to accomplish effective protection of EU financial interests. The establishment of the European Public Prosecutor’s Office and its material competences is burdened with some important issues: vagueness in prescribing criminal offences affecting the financial interests of the Union, problems with interpretation of the terms inextricably linked offences and offences regarding participation in a criminal organization if the focus of the criminal activity of such a criminal organization is to commit any of the offences affecting the financial interests of the Union.